CRIMINAL RESPONSIBILITY FOR CRIMES BASED ONARTIFICIAL INTELLIGENCE FROM THE PERSPECTIVE OF INDONESIAN CRIMINAL LAW - Hendri Saputra Manalu; Rahmayanti; Tita Rosmawati (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The rapid development of Artificial Intelligence (AI) technology has complex legal implications, particularly in the field of criminal law. Crimes committed using AI systems such as deepfakes, automated cyber attacks, algorithm-based fraud, and data manipulationraises fundamental questions about who should be held criminally responsible. This study aims to analyze the concept of criminal liability for AI-based crimes within the existing Indonesian criminal law framework and identify existing legal gaps (leemten in het recht). The research method used is normative juridical with a statute approach, a conceptual approach, and a comparative approach. The results show that the Criminal Code (KUHP) and Law Number 19 of 2016 concerning Information and Electronic Transactions (ITE) have not been able to optimally address criminal liability for crimes mediated by autonomous AI systems. Comprehensive regulatory reform is needed, including the determination of new legal subjects, the implementation of adapted strict liability and vicarious liability doctrines, and the establishment of a specific legal framework related to AI. This study recommends the drafting of an Artificial Intelligence Bill that explicitly regulates aspects of criminal liability in the AI ​​ecosystem.